The Relationship Between Peer Social Support and Self-Regulated Learning in Vocational High School Students: Hubungan Antara Dukungan Sosial Teman Sebaya dengan Self Regulated Learning pada Siswa di Sekolah Menengah Kejuruan - Khusniyah, Wardah; Widyastuti, Widyastuti (Universitas Muhammadiyah Sidoarjo, 2022)
This research was conducted because of a phenomenon that shows low self-regulated learning by showing behaviors such as lack of enthusiasm in learning. The purpose of this study was to determine whether there was a relationship between peer social support and self-regulated learning in students at SMK Antarctica 2 Sidoarjo. The sampling technique in this research uses proportional stratified random sampling. The research technique is a correlational quantitative method. The research sample as many as 304 students obtained with a significance level of 5% of the total population of 2,470 students. The data collection method uses 2 psychological scales, namely the peer social support scale with a reliability of 0,901, and self-regulated learning scale with a reliability 0,901. The proposed hypothesis is that there is a significant positive relationship between peer social support and self-regulated learning. Analysis of the data with Correlation Product Moment Pearson. The result, r = 0.197, p = 0.000 (p < 0.05), which means the research hypothesis is accepted. The higher the peer social support, the higher the self-regulated learning. On the other hand, the lower the peer social support, the lower the self-regulated learning of the students of SMK Antartika 2 Sidoarjo. The contribution of peer social support to the occurrence of self-regulated learning is 14,6%.